Razvojni program celovitega in trajnostnega razvoja območja Prezida in Gorskega kotarja (University of Maribor Press, 2018)
The Development Program of Comprehensive and Sustainable Development of the Prezid and Gorski Kotar Area. The development program includes a broad overview of the destination, which is located in the border area between the Republic of Slovenia and the Republic of Croatia. Throughout the centuries, local residents have always connected the two countries. Likewise, the development program sees the key advantage and opportunity of the destination in interconnecting the locals while also working with other communities. Another advantage that makes this tourist destination attractive is a pure and unspoilt nature that enables recreation, relaxation in nature and learning about the local flora and fauna. If we add to this the cultural heritage, folk tradition and local gastronomy, the destination can offer a complete package to the tourist. The development program acknowledges many potentials in the destination, but the destination must follow the principles of sustainable development in order to preserve the authenticity and integrity. This challenge was addressed by students of the 1st year Master’s program Tourism at the Faculty of Tourism University of Maribor. In addition to their analysis of the destination, their insights and proposals, they also prepared an action plan on how to realize the vision of sustainable development. Thus, this document was created, which in its first part gives a theoretical background of sustainable development and finally concludes with an overview of the measures for the concrete example of Prezid and Gorski kotar destination.